Comparison of clinical outcomes of venous thromboembolic disease between outpatient and inpatient management - Gregalio, Felipe Aníbal (2024)
Objectives. To compare the occurrence of death, bleeding, and recurrence according to inpatient or outpatient management of venous thromboembolic disease (VTE). Materials and methods. Retrospective cohort that included a consecutive sampling of VTE consultations between 2016 and 2019 diagnosed in the Emergency Center of a private hospital in Argentina. Results. There were 1202 cases, 908 with isolated deep vein thrombosis (DVT), 205 with isolated pulmonary embolism (PE), and 89 cases of combined DVT - PE. 66% were women, with a median age of 77 years; 72% of cases were managed on an outpatient basis (n= 862). Comorbidities associated with hospitalization were obesity (p=0.03), chronic obstructive pulmonary disease (COPD) (p=0.01), heart failure (CHF) (p=0.01), chronic renal failure (CKD) (p=0.01), and cancer (p=0.01). At 90 days, the cumulative incidence of bleeding was 2.6% in inpatient compared to 2.9% in outpatient management (p=0.81); recurrence was 0% versus 0.9% (p=0.07), and mortality was 42.9% versus 18.9%, respectively (p=0.01). The HR for 90-day mortality in hospitalized patients adjusted for confounders (sex, age, type of VTE, obesity, CKD, CHF, COPD, and cancer) was 1.99 (95% CI 1.49-2.64; p=0.01). Conclusions. In this elderly, and predominantly female Argentine population, the 90-day mortality in patients hospitalized for VTE was higher than mortality in patients with outpatient management, without differences in recurrence or major bleeding.